Gypsum flocculation experiment in river Paimionjoki, Finland, 2022 - Samu Elovaara; Lingbin Zhao; Eero Asmala; Hermanni Kaartokallio; David N Thomas (PANGAEA, 2025)
A laboratory experiment was conducted to investigate gypsum induced flocculation of dissolved organic matter in a boreal river Paimionjoki in south-western Finland in April, May, June and August 2022. The purpose was to investigate particulate matter formation caused by gypsum induced-flocculation and changes in the characteristics and bioavailability of the dissolved organic matter pool. The experiment included water sampling and measurements close to the estuary (doi:10.1594/PANGAEA.967417 and doi:10.1594/PANGAEA.967427), a flocculation experiment in the laboratory (doi:10.1594/PANGAEA.967423), an ultrafiltration of the water generated during the flocculation experiment (doi:10.1594/PANGAEA.967424) and a bioassay incubation using the water generated during the flocculation experiment (doi:10.1594/PANGAEA.967426). The flocculation experiment was conducted as a jar experiment using Velp Scientifica FC6S flocculator (1 h at 60 RPM). Two treatments were used in the experiment, a gypsum treatment where calcium sulfate (14.8 mmol/l, final concentration 1.48 mmol/l) was added to the samples and a control treatment where ultrapure water was added instead. Water sample collection and sensor measurements were conducted immediately below water surface. All experiments were conducted in 10 C.